The printing revolution in early modern Europe - Eisenstein, Elizabeth L. (Canto classics., 2021)
In 1979 Elizabeth Eisenstein provided the first full-scale treatment of the fifteenth-century printing revolution in the West in her monumental two-volume work, The Printing Press as an Agent of Change. This abridged edition, after summarising the initial changes introduced by the establishment of printing shops, goes on to discuss how printing challenged traditional institutions and affected three major cultural movements: the Renaissance, the Reformation, and the rise of modern science. Also included is a later essay which aims to demonstrate that the cumulative processes created by printing are likely to persist despite the recent development of new communications technologies.